Markov Chain Prediction of the Long-Run Behavior of Nigerian Oil Stock - Jude, Iroka; Mamidu, Moses Joanna (Mikailalsys Journal of Mathematics and Statistics, 2025)
This study examined the behavior and long-term prospects of selected Nigerian oil stocks such as Conoil, Seplat Oil, and Total Oil by analyzing their daily closing prices using the Chi-Square test for independence, transition probability matrices, and steady-state probability analysis. The Chi-Square test revealed a significant dependence between the daily closing prices of the stocks, indicating a correlation between subsequent price movements. The transition probability matrices showed that Conoil and Seplat Oil have an equal likelihood of transitioning between the High (33.34%), Stable (33.33%) and Low (33.33%) price states, while Total Oil demonstrated a stronger preference for the High (41.92%) , stable (36.71%) and low (21.37%) states. The steady-state probabilities revealed that Conoil and Seplat Oil and Total Oil have a higher likelihood of remaining in the high state in the long term, with Total Oil exhibited a more balanced distribution, suggesting a more stable price movement. The findings imply that investors should consider the correlation between daily price movements and the long-term behavior of these stocks. However, the study's limitations, such as the exclusion of external factors like global oil prices and political stability, should be taken into account when interpreting the results.